The Sociology of Intra-African Pastoralist Migration: The Case of Tanzania - Awinia, Christopher Simeon (Frontiers in Sociology, 2020)
Intra-African migration in sub-Saharan Africa is increasingly characterized by migration further and further south of the equator. The study focuses on the relationship between pastoralist migration and climate change, followed by loss of control of epidemics, which can lead to losses of large numbers of livestock. While increasing changes in the natural environment have been widely cited in the empirical literature, less attention has been paid to the social context and sociological factors influencing modern-day climate-induced intra-African pastoralist migration. Using Blumer's structural symbolic interaction as an analytic framework, this study examines how social and cultural perceptions influence subjective interpretations that lead to decision points that trigger intra-African pastoralist migration. Using structural symbolic interaction as an analytic framework to study interrelationships between climate-induced stimulus, symbolic interpretation, and migration response, the study identifies that decisions to migrate to other ecosystems were mediated through symbolic signs with assigned meaning and significance communicated through language, signs, symbols, ritual, and religion, which makes up the overall pastoralist cosmology of migration. That these signs and meanings, which are given symbolic meaning, form the basis of African pastoralist sociology of migration. These are the key factors that explain why some pastoralist households decide to migrate to other ecological zones while others remain in traditional pastoralist lands. This study was guided by two hypotheses. The first is that intra-African pastoralist migration is socially defined based on the social and cultural perceptions and meanings attached to interactions with their increasingly changing natural and social circumstances (H1). The second (H2) is that this meaning is defined and modified through an interpretative process in response to changing social and natural circumstances. The sample examined in the study covered seven districts with a high proportion of pastoralists across four eco-climatic zones. A total of 544 pastoralist households were interviewed. In-depth qualitative interviews and observation studies were conducted in three case-study villages. The study concludes that decisions to migrate to other ecosystems are mediated through symbolic signs with assigned meanings and significances communicated through language, signs, symbols, rituals, and religion. Together, these findings contribute to our further understanding of the sociology of recent intra-African migration.